Multicentre randomised controlled trial of nasal diamorphine for analgesia in children and teenagers with clinical fractures - Kendall, Jason M (BMJ, 2001)
OBJECTIVE: To compare the effectiveness of nasal diamorphine spray with intramuscular morphine for analgesia in children and teenagers with acute pain due to a clinical fracture, and to describe the safety profile of the spray. DESIGN: Multicentre randomised controlled trial. SETTING: Emergency departments in eight UK hospitals. PARTICIPANTS: Patients aged between 3 and 16 years presenting with a clinical fracture of an upper or lower limb. MAIN OUTCOME MEASURES: Patients' reported pain using the Wong Baker face pain scale, ratings of reaction to treatment of the patients and acceptability of treatment by staff and parents, and adverse events. RESULTS: 404 eligible patients completed the trial (204 patients given nasal diamorphine spray and 200 given intramuscular morphine). Onset of pain relief was faster in the spray group than in the intramuscular group, with lower pain scores in the spray group at 5, 10, and 20 minutes after treatment but no difference between the groups after 30 minutes. 80% of patients given the spray showed no obvious discomfort compared with 9% given intramuscular morphine (difference 71%, 95% confidence interval 65% to 78%). Treatment administration was judged acceptable by staff and parents, respectively, for 98% (199 of 203) and 97% (186 of 192) of patients in the spray group compared with 32% (64 of 199) and 72% (142 of 197) in the intramuscular group. No serious adverse events occurred in the spray group, and the frequencies of all adverse events were similar in both groups (spray 24.1% v intramuscular morphine 18.5%; difference 5.6%, –2.3% to 13.6%). CONCLUSION: Nasal diamorphine spray should be the preferred method of pain relief in children and teenagers presenting to emergency departments in acute pain with clinical fractures. The diamorphine spray should be used in place of intramuscular morphine.